Selective etching of Sm0.5Sr0.5CoO3-δ ceramic for solar evaporator with photocatalytic purification. (15th May 2022) - Gao, Yalin; He, Yongshuai; Zhou, Hong; Yin, Jialiang; Fang, Zhenggang; Lu, Chunhua; Xu, Zhongzi
Graphical abstract: Highlights: The photo-thermal conversion material (Sm0.5 Sr0.5 CoO3-δ ) carrying catalytic material (Co3 O4 ) was prepared via a facile one-step nitric acid etching method. The surface of Sm0.5 Sr0.5 CoO3-δ was selectively reconstructed through the acid-etching treatment and then the catalytic active cobalt cation was randomly exposed. The acid-etched Sm0.5 Sr0.5 CoO3-δ exhibited a higher solar absorbance and better catalytic ability, which showed promising application in the pure water production. Abstract: The ultimate goal of solar driven water evaporation is to obtain clean water without volatile organic pollutants. Current strategies mainly depend on the integration of the photo-thermal conversion and photocatalytic degradation by a multi-step composite technique. In this work, a facile nitric acid etching method was adopted to prepare the photothermal-catalytic bifunctional material (Sm0.5 Sr0.5 CoO3-δ -Co3 O4 ). The effect of the acid-etching treatment on the Sm0.5 Sr0.5 CoO3-δ surface evolution was investigated. The Sm0.5 Sr0.5 CoO3-δ (SSC5) surface was selectively reconstructed, and the catalytic active B-site cobalt cation was randomly exposed after the acid-etching treatment. The unique structure of SSC5-Co3 O4 was beneficial to the electrons transport between Co3 O4 and SSC5, as well as the solar absorbance. The nitric acid-etched SSC5 honeycomb ceramic exhibited a solar absorption of 80%, resulting in an evaporation rate of 7.25 kg·m −2 ·h −1 under a simulated sunlight of 1000 mW·cm −2 . Besides, the etched SSC5 exhibited the ability for pollutant (Congo red) degradation. The as-prepared acid-etched SSC5 honeycomb ceramic could integrate the solar evaporation with pollutant degradation, which has a promising application in the pure water production.